2020
DOI: 10.3390/ijms21197290
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Degeneration and Alzheimer’s Disease: An Evolving Link

Abstract: Age-related macular degeneration (AMD) and glaucoma are degenerative conditions of the retina and a significant cause of irreversible blindness in developed countries. Alzheimer’s disease (AD), the most common dementia of the elderly, is often associated with AMD and glaucoma. The cardinal features of AD include extracellular accumulation of amyloid β (Aβ) and intracellular deposits of hyper-phosphorylated tau (p-tau). Neuroinflammation and brain iron dyshomeostasis accompany Aβ and p-tau deposits and, togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 155 publications
0
78
2
Order By: Relevance
“…Calpain-1 is involved in the cleavage of tau protein at multiple sites that contribute to both clearance and accumulation of fibril formation [ 35 ]. Intriguingly, Alzheimer's disease is often associated with age-related macular degeneration and glaucoma, and common features including amyloid β plaque deposition, chronic inflammation, iron accumulation, and oxidative stress have been reported [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calpain-1 is involved in the cleavage of tau protein at multiple sites that contribute to both clearance and accumulation of fibril formation [ 35 ]. Intriguingly, Alzheimer's disease is often associated with age-related macular degeneration and glaucoma, and common features including amyloid β plaque deposition, chronic inflammation, iron accumulation, and oxidative stress have been reported [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hallmark pathology of AMD is ocular drusen and extracellular deposits located between the retinal pigment epithelium (RPE) and Bruch's membrane [12]. Similar to senile plaques in AD, Aβ is also an important constituent in drusen [13][14][15]. Previous study has demonstrated that the Aβ in drusen correlates with the location of photoreceptors and RPE cell degeneration [16].…”
Section: Introductionmentioning
confidence: 99%
“…Prion and “prion-like” diseases are known to cause retinal damage in humans and other species, but each disease affects the retina in unique ways [ 44 ]. In Alzheimer’s disease patients, Aβ deposition has been associated with degeneration of the retinal ganglion cell layer, photoreceptors and the retinal pigmented epithelium [ 3 , 45 ]. Ratnayaka et al have also shown that Aβ plaques may be a key factor in Age-related Macular Degeneration (AMD).…”
Section: Introductionmentioning
confidence: 99%